Essentials of sports performance training - McGill, Erin A.; Montel, Ian (Jones and Bartlett, 2019)
"New Content Based upon feedback from past students and Sports Performance Professionals, this new textbook includes several new updates in comparison to the previous performance enhancement materials: 1. Streamlined OPTTM Model--The OPTTM model has been simplified to include six of the most commonly used phases of training for sports performance goals, versus the previous seven-phase model. The one phase of training that is no longer included in this performance version of the model, Corrective Exercise Training, is a specialized form of training that would be used for athletes who've come off an injury and prepares the athlete to enter into the OPTTM model. This form of training is covered exclusively in NASM's Corrective Exercise Specialist course. 2. Revised Model Nomenclature--We've also renamed the phases so it is easier to understand the exact function and desired adaptation for that phase of training. 3. Additional Chapters--This textbook includes several new chapters not included in the previous performance enhancement materials. These additional chapter topics will assist in creating a more well-rounded Sports Performance Professional and thus in creating more value in you as a professional. These additional chapters include: ? Cardiorespiratory Training for Performance Enhancement ? Olympic Lifting for Performance Enhancement ? Current Concepts in Injury Prevention and Reconditioning ? Ergogenic Aids ? Sports Psychology"--